EFL STUDENTS’ ACHIEVEMENT AND MOTIVATION IN WRITING TEXT THROUGH WEBBING TECHNIQUE - Antiyastuti, Dwi (Teaching English as a Foreign Language Overseas Journal, 2022)
The objectives of the research were to find out whether or not the use of webbing technique can improve the writing skill of second year students of SMP Negeri 8 Makassar and to know how the motivation students in writing skill through webbing technique. The writer  was applied pre experimental with one group pre-test and post-test. This research was conducted at SMP Maha Putra Makassar sub-district of Panakukang, Makassar city. In this research, the population was the eight grade students of SMP Maha Putra Makassar in academic year 2021/2022. The total numbers of population were 360 students. The researcher was used total sampling technique. The total number of sample was 40 students from class VIII-1. In analyzing the numerical data, the writer used SPSS for windows.  After conducted the research, the writer concludes that that The use of webbing in teaching writing skills enriches the students’ achievement; it is proved by the mean score of the students’ in pre-test and posttest. The mean score of the pre-test before the treatment was 61.72 and after the treatment the students gained score 74.88. The t-test of the students’ achievement in posttest was smaller than ?. The researcher found that the p-value (probability value) was lower than ? (0.00 < 0.05) and the degree of freedom was 39. The t-test value of pre-test and post-test was remarked significantly different.  It indicated that the alternative hypothesis (H1) was accepted and, of course, the null hypothesis (H0) was rejected. The use of webbing technique can improve students motivation in learning writing skills